Peran Tax Awareness Dalam Memoderasi Money Ethics Dan Discrimination Terhadap Niat Tax Evasion (Studi Empiris Wajib Pajak Orang Pribadi DKI Jakarta Tahun 2023) - Putri Kusuma Jati; Bambang Subianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze and obtain empirical evidence of the role of Tax Awareness in moderating the influence of Money Ethics and Discrimination on Tax Evasion intentions. The population in this study is individual taxpayers. The sampling technique used is Purposive Sampling with 100 individual taxpayers obtained. The data analysis method used in this study is Structural Equation Modeling (SEM) and the data is processed with the help of the SMARTPLS program version 3.0. The test results show that the Money Ethics variable does not affect Tax Evasion, but the discrimination variable affects Tax Evasion. Tax Awareness is said to be unable to moderate the variables of Money Ethics and Discrimination in Tax Evasion. Based on the results of the analysis, it can be concluded that one of the factors that influence the occurrence of Discrimination Action against Tax Evasion, namely an unfair behavior or action carried out by the tax fiscus against taxpayers. This affects taxpayers to carry out Tax Evasion actions and perceive these actions to be ethical even though they can harm the state. Money Ethics does not affect Tax Evasion nor can Tax Awareness moderate the relationship between Money Ethics and Discrimination. This is because there are still many taxpayers who obey tax regulations not on the basis of self-awareness and can also be caused because the tax rate is too high. Keywords: Tax Awareness, Money Ethics, Discrimination, Tax Evasion